2021
DOI: 10.1038/s41467-021-25847-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic hydrogel nanoparticles for sepsis therapy

Abstract: Sepsis is a life-threatening condition caused by the extreme release of inflammatory mediators into the blood in response to infection (e.g., bacterial infection, COVID-19), resulting in the dysfunction of multiple organs. Currently, there is no direct treatment for sepsis. Here we report an abiotic hydrogel nanoparticle (HNP) as a potential therapeutic agent for late-stage sepsis. The HNP captures and neutralizes all variants of histones, a major inflammatory mediator released during sepsis. The highly optimi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…In general, protein adsorption onto polymer particles is strongly influenced by the hydrophilicity/hydrophobicity and charge of their surfaces. 58–60 Zwitterionic MPC-based polymers suppress nonspecific protein adsorption because their chains are extremely hydrophilic and neutral, and hydrated with water molecules having a specific state. 24,31,34 Therefore, the lack of FITC-BSA adsorption onto the maleimide-P(St- co -MAA- co -MPC) particle-assembled film is based on the zwitterionic MPC chain on the particle surface.…”
Section: Resultsmentioning
confidence: 99%
“…In general, protein adsorption onto polymer particles is strongly influenced by the hydrophilicity/hydrophobicity and charge of their surfaces. 58–60 Zwitterionic MPC-based polymers suppress nonspecific protein adsorption because their chains are extremely hydrophilic and neutral, and hydrated with water molecules having a specific state. 24,31,34 Therefore, the lack of FITC-BSA adsorption onto the maleimide-P(St- co -MAA- co -MPC) particle-assembled film is based on the zwitterionic MPC chain on the particle surface.…”
Section: Resultsmentioning
confidence: 99%
“…The use of polymer/molecular support with uniform structure such as uniform polymers [54,55] dendrimers, [51,56,57] precision oligomers [34,40,43,48] and biomacromolecules including peptides, [59] nucleic acids [35,58] and proteins [41,42] and would enable full control of the arrangement of oligomers. Target molecules in this study was limited to melittin, though, other target such as histone, [19] vascular endothelial growth factor (VEGF165) [3,20] aromatic peptides [7] and proteases [5] would be targeted by the same strategy. The strategy of using precise oligomer as a mimic of complementarity-determining region of immunoglobulins enables the development of "monoclonal plastic antibodies", synthetic materials with fully uniform binding structure for target recognition, that show highly specific and strong affinity to target biomacromolecules with less concern of side effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that NPs can recognize and neutralize target molecules in the bloodstream of living animals. [18][19][20] How-ever, sequences of functional monomers in the synthetic polymer NPs are heterogeneous. The sequence heterogeneity allows the production of NPs that function as broadspectrum antitoxins, but limits the target specificity and safety of the plastic antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…However, a single treatment does not provide a timely and effective antibacterial treatment. In order to promote precise effects, nano metal materials must be capable of intelligent function and morphologically designed, 38–40 such as hydrophilicity and targeted modification. 41 At the same time, they must overcome the disadvantages of poor targeting, 42–44 low permeability and weak diffusion in organisms, improve the biocompatibility and stability of materials, 45 and achieve efficient sterilization effects.…”
Section: Introductionmentioning
confidence: 99%